2022
DOI: 10.1177/07356331221100740
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Game-Based Learning on Students’ Computational Thinking: A Meta-Analysis

Abstract: This meta-analysis determined game-based learning’s (GBL) overall effect on students’ computational thinking (CT) and tested for moderators, using 28 effect sizes from 24 studies of 2,134 participants. The random effects model results showed that GBL had a significant positive overall effect on students’ CT (g = 0.677, 95% confidence interval 0.532–0.821) with significant heterogeneity among effect sizes. Among game types, role-playing yielded the largest GBL effect size, followed by action, puzzles, and adven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…More specific positive learning gains were reported in a number of skills, e.g., problem-solving skills and pattern exploration skills (Higgins et al, 2012 ), metacognitive learning outcomes (Verschaffel et al, 2019 ), literacy skills, computational thinking skills, emotion control skills, and collaborative inquiry skills (Lu et al, 2022 ; Su & Yang, 2022 ; Su et al, 2022 ). Additionally, several investigations have reported benefits from the use of ICT on students’ creativity (Fielding & Murcia, 2022 ; Liu et al, 2022 ; Quah & Ng, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…More specific positive learning gains were reported in a number of skills, e.g., problem-solving skills and pattern exploration skills (Higgins et al, 2012 ), metacognitive learning outcomes (Verschaffel et al, 2019 ), literacy skills, computational thinking skills, emotion control skills, and collaborative inquiry skills (Lu et al, 2022 ; Su & Yang, 2022 ; Su et al, 2022 ). Additionally, several investigations have reported benefits from the use of ICT on students’ creativity (Fielding & Murcia, 2022 ; Liu et al, 2022 ; Quah & Ng, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…If not, the effect sizes were combined. For instance, if a study reported the effect size of a genderspecific group of students, the effect size of each group was calculated, assuming that each group was independent, and the participants did not overlap (Lipsey & Wilson, 2001). In particular, if a study reported multiple assessments of CT but not an overarching assessment, they were not considered independent outcomes but calculated as a combined effect size (Halme et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The issue of missing data is important in the coding of moderating variables. Studies that do not report certain item codes might yield implausible conclusions if they are discarded (Lipsey & Wilson, 2001). Therefore, we provided an "NA" option for these items.…”
Section: Coding Of Study Characteristics and Moderator Variablesmentioning
confidence: 99%
See 2 more Smart Citations